Java for Students
* Completely rewritten and expanded to contain 33% more pages that the first edition * Covers the latest I.C.S.E. 2011 onwards syllabus. * Additional material, including solved exam papers, online tests, and more, available on the companion web-site, http://www.ajaypherwani.com * Based on a teaching style that has worked successfully with students * Introduces every concept through examples * Loaded with actual screen shots that display the output of each program * Does not assume any prior knowledge of programming * Uses over 100 simple programs, that evolve line-by-line into more complex ones, in order to bring aboiut a complete understanding of the concept * Uses examples that a student would associate with in order to make the book more interesting â€" ice creams, super heroes, cricket, etc.